Field test and numerical investigation on thermal environment of tunnel with air layer structure. (October 2021) - Zhang, Guozhu; Cao, Ziming; Wang, Wei; Mei, Xuesong; Zhao, Xu; Shen, Shiwei; Na, Tongxing
Abstract: In this study, an air layer structure is proposed for controlling the thermal environment in high ground temperature tunnels, and for meeting the environmental requirements during tunnel construction. Thermal response field experiments on a mountain tunnel equipped with an air layer structure were conducted under tunnel ventilation and heating. The variations in air temperature inside the tunnel and thermal response characteristics of the surrounding rock at the condition of tunnel with an air layer structure were analyzed. Moreover, the effects of the tunnel ventilation and type of air layer on the thermal insulation performance of the air layer structure were evaluated in detail. Based on the theoretical analysis, the heat transfer pattern of the air layer structure was discriminated. Good consistency was found between the theoretical and experimental results for the discrimination of the thermal insulation performances of different types of air layers. Finally, the heat transfer process of the tunnel with the air layer structure was simulated and analyzed by establishing a numerical model. The results show that the numerical results regarding the temperature fields within the tunnel are in good agreement with the measured results, and that a high ground temperature tunnel with an air layer structure has a preferable thermal insulation effect. Highlights: Field tests of tunnel with the air layer structure are performed under tunnel heating and ventilation. Air temperature and surrounding rock temperature of tunnel with the air layer structure are studied. Thermal insulation performance of tunnel with the air layer structure is analyzed. Heat transfer pattern of the air layer structure is discriminated. Heat transfer process of tunnel with the air layer structure is simulated and analyzed.